All i want for christmas is a cowboy eaudiobook - Clare, Jessica (Wyoming Cowboys, 2019)
Christmas may be coming, but it's just another day at the ranch as far as Eli Pickett is concerned. Someone has to take care of the herd and that means no holiday vacation for him. But that's just the way he likes it—it's not like he has a woman to spend time with anyways. Most women don't want the ranch life, or the surly, silent cowboy that comes with it. Fine with him. He'd rather have the quiet of a roaring fire and the company of his dogs. Cassandra Horn is trying to make it to her parents' winter cabin in Wyoming before the blizzard hits. She desperately needs a vacation from the chaos of Manhattan . . . and her boss's boyfriend, who is making her life miserable. But Cass never makes it to the cabin. A raging snowstorm causes her car to crash, where she's found unconscious by Eli. When Cass wakes, she has no memories of who she is. Eli takes one look at Cass's big blue eyes and dark curls, and like a Christmas miracle, falls head over heels in love. But while the attraction is mutual, can she give her heart to this cowboy if she's not sure it's hers to give? Contains mature themes.